Meningkatkan Aktivitas Dan Keterampilan Berpikir Kritis Pada Muatan IPAS Dengan Model Panting Siswa Kelas V SDN Danda Jaya 2 - Riska Aulia Utami; Akhmad Riandy Agusta; Fathul Jannah; Ari Hidayat (CV. ITTC INDONESIA, 2024)
Students critical thinking activities and skills are still relatively low. For this reason, an effort was made to overcome this problem by using the PANTING model which is a combination of the Problem Based Learning, Two Stay Two Stray, and Mind Mapping learning models. This research aims to improve the learning process by increasing activity, critical thinking skills, and student learning outcomes through a PANTING learning model. The research implemented Classroom Action Research (PTK) which was carried out in 4 meetings. The data collected is qualitative data obtained from observing student activities, teacher activities, and critical thinking skills as well as quantitative data obtained from student learning outcomes. The results of this research show that there has been an increase in teacher activity, student activity, critical thinking skills, and learning outcomes at each meeting. Until finally at the fourth meeting all aspects had achieved the specified success criteria. This improvement makes the learning process even better. Based on the results of the research that has been carried out, it can be concluded that the PANTING model can increase students' activities, critical thinking skills and student learning outcomes.